2013
DOI: 10.1146/annurev-animal-031412-103651
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of B Cell Immunity

Abstract: Two types of adaptive immune strategies are known to have evolved in vertebrates: the VLR-based system, which is present in jawless organisms and is mediated by VLRA and VLRB lymphocytes, and the BCR/TCR-based system, which is present in jawed species and is provided by B and T cell receptors expressed on B and T cells, respectively. Here we summarize features of B cells and their predecessors in the different animal phyla, focusing the review on B cells from jawed vertebrates. We point out the critical role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
84
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(86 citation statements)
references
References 172 publications
(259 reference statements)
1
84
0
1
Order By: Relevance
“…In contrast, B-2 cells are a major B cell population circulating throughout the entire body and producing highaffinity Ag-specific Abs in a T cell-dependent manner (51,52). As one of the most important cellular components in the immune system, the origin and evolution of B cells have received considerable attention (53,54). However, this topic has long been challenged in immunology given the limited information about B cells in phylogenetically older species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, B-2 cells are a major B cell population circulating throughout the entire body and producing highaffinity Ag-specific Abs in a T cell-dependent manner (51,52). As one of the most important cellular components in the immune system, the origin and evolution of B cells have received considerable attention (53,54). However, this topic has long been challenged in immunology given the limited information about B cells in phylogenetically older species.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this finding led to the recent identification of a similar feature shared by B-1 cells in mammals, which points to the innate-like nature of B-1 cells, as well as the existence of a close evolutionary relationship between the ancient B cell lineage and the B-1 subset (10,11). Given the central function of an innate-like cell in nonspecific Ag presentation, this innate feature has been examined in detail in B-1 cells (53). However, it remains undetermined whether fish B cells have such a function.…”
Section: Discussionmentioning
confidence: 99%
“…Teleost fish possess three major types of immunoglobulins: IgM and IgD, that have been identified in all teleost fish examined, as in almost all jawed vertebrates (Parra et al, 2013); and IgT (named as IgZ in cyprinids) which was identified in rainbow trout and zebrafish in 2005 (Danilova et al, 2005; Hansen et al, 2005), and has been found to be a specialized mucosal-dedicated immunoglobulin, akin to IgA and IgX in tetrapods and amphibians respectively (Zhang et al, 2010). The teleost igh locus encoding these three isotypes is arranged in a translocon organization (Flajnik and Kasahara, 2010).…”
Section: Immunoglobulins Of Teleost Fishmentioning
confidence: 99%
“…However, minor modifications of this archetypal structure of the genomic igh locus occurred in various teleost species (Bengtén and Wilson, 2015; Fillatreau et al, 2013). Importantly, in sharp contrast to tetrapod igh locus that is regulated by an AID-mediated class switch recombination, the genomic structure of teleost igh locus rules out a possible class switch recombination between ighτ/ζ and ighμ , leading to the development of mutually exclusive B-cell lineages expressing IgT or IgM/D (Parra et al, 2013; Zhang et al, 2010). In support of this, B cells uniquely expressing surface IgT or IgM have been described in rainbow trout (Zhang et al, 2010).…”
Section: Immunoglobulins Of Teleost Fishmentioning
confidence: 99%
See 1 more Smart Citation